2020
DOI: 10.3389/fpsyg.2020.520703
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions of New Zealand Lawyers and Social Workers About Children Being Adopted by Gay Couples and Lesbian Couples

Abstract: normalizing same-gender parenting is what needs to happen next. Our study adds to the research focused on adoption professionals in various countries, with the ultimate aim to inform practices and policies supportive of families headed by same-gender couples and formed through adoption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 90 publications
(136 reference statements)
1
1
1
4
Order By: Relevance
“…In summary, the results show that despite negative attitudes towards marriage and adoption by homosexuals, positive attitudes predominated, unlike previous studies that identified a predominance of opposing attitudes (Scherman et al, 2020;Tomczak & Zawadzka-Witt , 2021;Gato & Fontaine, 2016), including from people with religious beliefs (Gross et al, 2018;Lee & Multz, 2019;Vecho et al, 2016;Whitehead & Perry, 2016).…”
Section: Final Considerationscontrasting
confidence: 93%
See 2 more Smart Citations
“…In summary, the results show that despite negative attitudes towards marriage and adoption by homosexuals, positive attitudes predominated, unlike previous studies that identified a predominance of opposing attitudes (Scherman et al, 2020;Tomczak & Zawadzka-Witt , 2021;Gato & Fontaine, 2016), including from people with religious beliefs (Gross et al, 2018;Lee & Multz, 2019;Vecho et al, 2016;Whitehead & Perry, 2016).…”
Section: Final Considerationscontrasting
confidence: 93%
“…These comments were still characteristically delivered by participants politically aligned to the far right, which is congruent with international studies (Scherman et al, 2020) and reflects what Quintão (2017) affirms about the growing conservative wave of the far right in the Brazilian political scenario, especially in the Chamber of Deputies, where the Evangelical Parliamentary Front has been articulating since 1986 in defense of its agendas. These, most of the time, imply the obstruction of the path towards the conquest of rights and the legitimization of LGB identities, such as the right to civil marriage and adoption by persons of the same sex.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Esses discursos foram ainda caracteristicamente emitidos por participantes alinhados politicamente à extrema direita, o que é congruente com estudos internacionais (Scherman et al, 2020) e reflete o que Quintão (2017) afirma a respeito da crescente onda conservadora da extrema direita no cenário político brasileiro, especialmente na Câmara dos Deputados, onde a Frente Parlamentar Evangélica se articula desde 1986 em defesa de suas pautas. Essas, na maioria das vezes, implicam na obstrução do caminho rumo à conquista de direitos e à legitimação das identidades LGBs, como o direito ao casamento civil e a adoção por pessoas do mesmo sexo.…”
Section: Discussionunclassified
“…Apesar disso, a literatura científica revela a persistência da oposição aos direitos ao casamento e à adoção por LGBs. Num estudo realizado na Nova Zelândia, advogados e assistentes sociais demonstraram terem preferência a verem crianças adotadas por casais heterossexuais em detrimento de casais do mesmo sexo, sendo a religiosidade e o conservadorismo político associados a visões negativas em relação à adoção homoparental (Scherman et al, 2020). De forma análoga, um estudo na Polônia analisou as atitudes dos poloneses a respeito da legalização da união civil entre pessoas do mesmo sexo, encontrando que esse direito não é apoiado pela maioria da população (Tomczak & Zawadzka-Witt, 2021).…”
Section: Atitudes Sobre Os Direitos Ao Casamento Civil E à Adoção Por...unclassified